Cost‐effective upgrade of the Dutch traction power network: Moving to Bi‐directional and controllable 3 kV DC substations for improved performance - Nanda Kishor Panda; Michail Poikilidis; Phuong H. Nguyen (IET Electrical Systems in Transportation)
Abstract Traction power networks can significantly influence a country's national grid due to their significant power consumption and numerous coupling points. To modernise the ageing Dutch traction power networks and enhance their impact on the utility grid, this study explores practical and cost‐effective approaches for upgrading existing 1.5 kV DC traction substations (TS) in the Netherlands into 3 kV bi‐directional DC TS. After evaluating the benefits of a 3 kV bi‐directional DC, two novel topologies are proposed that re‐use the existing substation's components and reduce the need for higher investments. These topologies incorporate parallel voltage source converters (VSCs) to recuperate braking energy from the DC grid and transfer it back to the AC grid. Furthermore, the study investigates additional use cases for the VSCs, including improving DC TS's reliability during faults, reducing harmonics through active power filtering, compensating for reactive power, and supporting the integration of renewable energy sources into the DC grid. A comprehensive control strategy for the VSCs is also proposed based on a thorough analysis of their working methodology and functional modes. The feasibility and effectiveness of the proposed solutions are validated through scenario analysis relevant to the Netherlands' traction network, utilising both a Simulink model and an Opal‐RT real‐time simulator. This study serves as a starting point for the various stakeholders of the Dutch traction network in their journey towards modernising the current traction power supply. It has the potential to serve as a reference for reusing existing railway infrastructures to provide ancillary services and support the energy transition.